Mahasiswa dalam Belenggu AI: Praktik Konsumsi ChatGPT dan DeepSeek - Siti Umaiyah; Rino Andreas; Rony K. Pratama; Septi Anggita Kriskartika; Muhamad Reznu Firsyawardana (Laboratory of Anthropology Department, Faculty of Humanity, Halu Oleo University, 2025)
The rapid advancement of technology has brought significant changes to everyday life. Various activities that previously required human skills can now be gradually replaced by artificial intelligence (AI), such as text generation, language translation, and answering complex questions, which can now be done by platforms such as ChatGPT and DeepSeek. This study seeks to examine in greater depth the forms of acceptance and consumption patterns of ChatGPT and DeepSeek among university students. As an academic group, students have their own interpretations of the presence of these two technologies. This study uses a reception analysis method involving ten informants who belong to Generation Z, and refers to the decision-making theory proposed by George R. Terry and Brinckloe. The results of the study show that the audience has diverse interpretations of ChatGPT and DeepSeek consumption, which are influenced by their respective backgrounds and levels of knowledge. Most informants are in a position of negotiation, while others are in a dominant position that supports the use of AI in the field of higher education.